Residence in segregated settlements (colonies) rather than Roma identity increases the risk of unfavourable mental health in Hungarian adults - Oláh, Barnabás; Bíró, Éva; Kósa, Karolina (Frontiers in Public Health, 2023)
Background: Roma are the largest and most disadvantaged minority in Europe, but there is few research on how mental health and social support of Roma people living in segregated settlements compares to the majority population. Our aim was to compare the subjective well-being, life satisfaction, mental status, and social support of representative samples of adults living in segregated settlements (colonies) and identifying as Roma with those of the general population in Hungary.A cross-sectional study was conducted with random samples of 417 individuals from the general Hungarian adult population (55.6% female, mean age = 43.89 ± 12.61 years) and 394 adults living in segregated settlements (colonies) (73.9% female, mean age = 42.37 ± 12.39 years). Demographic questions were used as well as the WHO Well-Being Index (WBI-5), the single item Life Satisfaction Scale, the 12-item version of the General Health Questionnaire (GHQ-12), and the Oslo Social Support Scale (OSSS-3).Results: Residents of colonies reported significantly lower levels of subjective well-being and life satisfaction than the general population. The proportion of individuals at high risk for mental morbidity was more than twice as high among colony dwellers (16.4%) as in non-colony dwellers (7.6%). Similar unfavourable differences were seen at the expense of self-identified Roma compared to self-identified Hungarians but no difference was found in terms of social support either by type of residence or ethnicity. 32.2% of colony-dwellers self-identified themselves as Hungarian. Mental health assessed by principal component was directly determined by settlement type of permanent residence, age, educational attainment, employment, financial status, and social support but not ethnic identity.The study based on representative data shows that residents of segregated settlements are in worse mental health than those not living in colonies; that housing segregation is not limited to Roma people, and that housing conditions and financial status are major social determinants of mental health for which data must be collected to avoid using self-reported Roma identity as a proxy measure of socioeconomic deprivation.